Application of immunoaffinity columns for different food item samples preparation in micotoxins determination - Ćurčić Marijana; Ljubičić Žaklina; Vuković Gorica; Antonijević Biljana; Bulat Zorica; Matović Vesna (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
In analytical methods used for monitoring of what special attention is paid to sample preparation. Therefore, the objective of this study was testing the efficiency of immunoaffinity columns (IAC) that are based on solid phase extraction principles used for samples preparation in determining aflatoxins and ochratoxins. Aflatoxins and ochratoxins concentrations were determined in totally 56 samples of food items: wheat, corn, rice, barley and other grains (19 samples), flour and flour products from grain and additives for the bakery industry (7 samples), fruits and vegetables (3 samples), hazelnut, walnut, almond, coconut flour (4 samples), roasted cocoa beans, peanuts, tea, coffee (16 samples), spices (4 samples) and meat and meat products (4 samples). Obtained results indicate advantage of IAC use for sample preparation based on enhanced specificity due to binding of extracted molecules to incorporated specific antibodies and rinsing the rest molecules from sample which could interfere with further analysis. Additional advantage is the usage of small amount of organic solvents and consequently decreased exposure of staff who conduct micotoxins determination. Of special interest is increase in method sensitivity since limit of quantification for aflatoxins and ochratoxins determination method is lower than maximal allowed concentration of these toxines prescribed by national rule book.